A generic approach to scheduling and checkpointing workflows. (November 2019) - Han, Li; Le Fèvre, Valentin; Canon, Louis-Claude; Robert, Yves; Vivien, Frédéric
This work deals with scheduling and checkpointing strategies to execute scientific workflows on failure-prone large-scale platforms. To the best of our knowledge, this work is the first to target fail-stop errors for arbitrary workflows. Most previous work addresses soft errors, which corrupt the task being executed by a processor but do not cause the entire memory of that processor to be lost, contrarily to fail-stop errors. We revisit classical mapping heuristics such as Heterogeneous Earliest Finish Time and Min Min and complement them with several checkpointing strategies. The objective is to derive an efficient trade-off between checkpointing every task (Ckpt All ), which is an overkill when failures are rare events, and checkpointing no task (Ckpt None ), which induces dramatic re-execution overhead even when only a few failures strike during execution. Contrarily to previous work, our approach applies to arbitrary workflows, not just special classes of dependence graphs such as minimal series-parallel graphs. Extensive experiments report significant gain over both Ckpt All and Ckpt None for a wide variety of workflows.